Padrões de diversidade e estruturação das comunidades de anfíbios anuros no Parque Estadual do Mirador-MA - ANDRADE, Etielle Barroso de (2017)
This study aimed to evaluate the diversity patterns and structure of anuran’s communities in the Cerrado remnants of the Parque Estadual do Mirado-PEM, correlating environmental variables with distribution patterns of the species and identifying factors that determine the conservation status of the park. Although the PEM is located an area of great ecological importance, few studies were conducted on the biological communities, especially of amphibians. Thus, we perform a survey about the amphibian’s species describing the richness and composition of anuran fauna and analyzing the influence of different vegetation types in their formation. The sampling was carried out through active search and survey on breeding sites in different water bodies in the PEM, which resulted in the registration of 31 species belonging to five families: Leptodactylidae, Hylidae, Bufonidae, Microhylidae and Phyllomedusidae. Species richness in the PEM was greater than that recorded by several other authors in different regions of Brazil, being formed by typical Cerrado species and by species strongly associated with other biomes. The replacement of the species among the different water bodies was considered high in all combination pairs tested, even among the nearest water bodies. The results revealed a different use in vocalization sites, forming different groups with varying degrees of overlap, with environmental heterogeneity being the best criterion to explain the high diversity and spatial and temporal distribution of the species. Structurally complex environments have greater availability of resources and the composition of communities is regulated by the degree of overlap in the use of available microenvironments. The PEM is an important corridor bioregional conservation and understand the factors that act on the ecological and biogeographic processes of species are useful in the implementation of the management plan of the park and essential for the conservation of amphibians of the Maranhão state.